A interseccionalidade e suas contribuições para a compreensão do encarceramento de mulheres negras - Rosa, Camila Simões (Universidade Federal de São Carlos, 2018)
This is a theoretical study with a qualitative approach, and contributions in black feminism, which, when considering that there is no hierarchy between the practices of oppression experienced by women, recognizes the urgency of analyzes and reflections on the mass incarceration of black women. The context to be studied, and the theoretical option in Brazilian and North American black feminists, have leapfrogged the interest in a more detailed study of one of the concepts of this social movement, which guided by the invisibility of black woman agenda in feminist debates and on the race debates, proposes intersectionality. At the stage of the research that is dedicated to the understanding of this concept, historical discussions were conducted evidencing that black women were affected by intersectional discrimination even before the concept was outlined by Kimberlé Crenshaw in the 1980s. Presented here are the theoretical discussions of the concept from this North American feminist, Brazilian woman and others who collaborate in the theoretical impetus of intersectionality as analytical sensibility capable of taking from invisibility groups crossed by different practices of oppression. Also, in this discussion, there is a bibliographical survey in the thesis and dissertation bank of CAPES (Coordination of Improvement of Higher Level Personnel) amid the years 2005 and 2015 with the descriptor: intersectionality. The researches analysis regarded the number of publications per year, gender and race of the researchers, and the use of intersectionality in different contexts. Entering the intersectional discussion for the mass incarceration of black women, it presents an overview of women's prisons, an instrumental analysis of indicators of the female prison system, and considerations on the Women's Prison System from an intersectional perspective coming from Angela Davis. It evidences the potentiality of the intersectional concept in the understanding of experiences that affect black women and other marginalized groups. Moreover, this concept of black feminism arises as essential in the discussion of the oppression of gender and race that affect women in prison.

Se trata de un estudio de cuño teórico y abordaje cualitativo, con aportes en el feminismo negro, que al considerar no haber jerarquía entre las prácticas de opresión vivenciadas por mujeres, reconoce la urgencia de análisis y reflexiones sobre el encarcelamiento masivo de mujeres negras. El contexto a ser estudiado y la opción teórica en feministas negras brasileñas y norteamericanas, apalancar el interés en un estudio más profundo sobre uno de los conceptos de este movimiento social, que orientado por la invisibilidad de pautas de la mujer negra en los debates feministas y en los debates de raza, propone la interseccionalidad. En la etapa de la investigación que se dedica a la comprensión del concepto de interseccionalidad, se realizaron discusiones históricas que evidencian que las mujeres negras eran afectadas por las discriminaciones interseccionales incluso antes del concepto ser delineado por Kimberlé Crenshaw en la década de 80. Se presentan aún las discusiones teóricas del concepto a partir de esta feminista norteamericana, brasileñas y otras que colaboraron en el impulso teórico de la interseccionalidad como sensibilidad analítica capaz de sacar de la invisibilidad a grupos atravesados por diferentes prácticas de opresión. En esta discusión, se encuentra levantamiento bibliográfico en el banco de tesis y disertaciones de la CAPES (Coordinación de Perfeccionamiento de Personal de Nivel Superior) entre los de 2005 y 2015 con el descriptor "interseccionalidad". Las investigaciones fueron analizadas en relación a la cantidad de publicaciones por año, género y raza de los investigadores, y uso de la interseccionalidad en diferentes contextos. En el marco de la discusión interseccional para el encarcelamiento masivo de mujeres negras, se presenta un panorama de las prisiones femeninas, análisis instrumental de indicadores del sistema penitenciario femenino y consideraciones sobre el Sistema prisionero Femenino desde una perspectiva interseccional a partir de Angela Davis. Se evidencia la potencialidad del concepto interseccional en la comprensión de vivencias que afectan a mujeres negras y otros grupos marginados. Además, este concepto del feminismo negro surge como esencial en la discusión de las opresiones de género y raza que alcanzan a la mujer en situación de cárcel.
Intersectionality and its contributions to the understanding of black woman incarceration
La interseccionalidad y sus contribuciones para la comprensión del encarcelamiento de la mujer negra
Keywords: Interseccionalidade; Encarceramento em massa de mulheres negras; Mulheres negras; Intersectionality; Mass imprisonment of black women; Black women; Interseccionalidad; Encarcelamiento en massa de mujeres negras; Mujeres negras; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO